2022
DOI: 10.19127/bshealthscience.985870
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Rotavirus Infections

Abstract: Özet: Çocuklardaki akut gastroenterit etkenlerinin en önemlilerinden olan r otavirüsler zaman zaman hastanelerde, özellikle çocuk hastaların takip edildiği kliniklerde salgınlar yapabilir. Çocuk hastaların yanısıra bağışıklığı baskılanmış hastalar da bu enfeksiyon açısından risk altındadırlar. Bazı hastalar bu enfeksiyonu asemptomatik olarak da geçirebilse de, salgın kontrolünde bu hastaların da yönetimi oldukça önemlidir. Rotavirüs gastroenteritleri, mortalite, morbiditelerine ilave olarak artmış hastane mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…Rotavirus infections occur in Turkey throughout the year; however, they are usually more common between September and May [ 9 ]. Although infections do vary with respect to regions, a recent study reported rotavirus frequency to be between 7.7% and 73.7% [ 9 ]. The death rate due to diarrhea in Turkey decreased, following the widespread application of oral fluid treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Rotavirus infections occur in Turkey throughout the year; however, they are usually more common between September and May [ 9 ]. Although infections do vary with respect to regions, a recent study reported rotavirus frequency to be between 7.7% and 73.7% [ 9 ]. The death rate due to diarrhea in Turkey decreased, following the widespread application of oral fluid treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Even the nosocomial epidemics. Severe rotavirus gastroenteritis is seen in children who are usually immunosuppressed, unvaccinated, and aged between six months and two years of age 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Fekal oral yolla bulaşan bu patojenler kreş, bakımevi ve hastane klinikleri gibi ortak yaşam alanlarında hızla yayılarak salgınlara yol açabilmektedir. Çocuk kliniklerinde hastalar arasında bulaş nozokomiyal enfeksiyonlara neden olabilir (4) . Dolayısıyla enfekte kişilerin en hızlı şekilde belirlenerek izolasyon önlemlerinin alınması ve tedavi edilmesi yeni olguların hatta salgınların önlenmesinde çok önemlidir.…”
Section: Introductionunclassified